Application of intelligent rehabilitation equipment in occupational therapy for enhancing upper limb function of patients in the whole phase of stroke - Wenxi Li (Elsevier, 2021)
Stroke was one of the leading causes of death in the Chinese population in 2017. Most stroke survivors may suffer from different levels of disabilities, which prevents them from returning to their daily activities. The decreased upper limb function is considered as the principal factor that makes the patients have less access to their activities of daily livings. Occupational therapy (OT), aiming to enhance patients' functional performances and improve the participation in daily activities is usually applied from the onset of stroke. However, conventional OT intervention still has several problems that need to be solved, such as the inefficient use of human resources, inadequate upper limb functional training and non-continuous OT services. To address these difficulties and improve the patients' functional outcomes, intelligent rehabilitation equipment is combined with OT through evaluation and intervention. Based on this combination, OT can be provided in health care facilities, home, and community for patients with all phases of stroke. This combination promotes the transition of OT to digitization, intelligence and homogenization.